The Merchant of Venice : A Shakespeare Story - Matthews, Andrew; Retold by Andrew Matthews (UK Orchard Books, 2015)
The Merchant of Venice has been performed more often than any other comedy by Shakespeare. This edition pays special attention to the expectations of its first audience, and to our modern experience of seeing and hearing the play.
Include Illustration
Illustrated by Tony Ross
Keywords: Italy--Venice -- Merchant of Venice (Shakespeare, William)